First record of the Greenhouse frog, Eleutherodactylus planirostris (Anura: Eleutherodactylidae), in Costa Rica - Barquero Arroyo, Marco David (2016)
Introduced species can have a negative impact on native species, so that detection of new arrivals is fundamental to avoid establishment of breeding populations. Several species of frogs and lizards have been introduced into Costa Rica and the Caribbean coast has been a major entry for many species. Here we report the collection for the first time in the country of the Greenhouse frog, Eleutherodactylus planirostris. We believe that this species can become widespread in the Caribbean coast of Costa Rica and could be a new addition to the introduced herpetofauna.